Implementation of IPv6 With MAC Basis In Wireless LAN Network - Fransiscus A. Halim; Pujianto Yugopuspito; Robert A. Suhim (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
AbstractIt is now important to implement TCP/IP version 6 protocol (IPv6) in the network. Regarding to depletion of IPv4 address, the migration to IPv6 is crucial because the address space is shrinking day by day. Universitas Pelita Harapan (UPH) has a wireless LAN network which has been operating. Wireless LAN network is used as a facility to access the internet. UPH has implemented virtual LAN technology to accomodate a large number of users. Due to inefficient topology, VLAN cannot work efficiently. Wireless LAN network changes are necessary to overcome this inefficiency. The new design of wireless LAN network also considers the implementation of IPv6. The purpose of this thesis is to design the topology of wireless LAN in IPv6 basis.IPv6 implementation process is elaborated through creating an environment called test-bed. Test-bed is a small environment of network for testing purposes. All implementation processes are tested in this environment. Some testings were done to know the operating system’s support, how much time is needed for host to get configuration and protocol testing.There are 3 conclusions that can be drawn from the experiments. The first conclusion is not all operating systems support IPv6 by default. The second conclusion is the time needed by the host to get IPv6 address is 194.76 milisecond at zero traffic and 328.13 milisecond at full traffic. The third conclusion is DHCPv6 relay agent is not necessary due to time delay. The new topology is designed and ready to be implemented. Keyword : IPv6 implementation, medium access control, wireless LAN